Infrastructure and Private-Sector Productivity - Ford, Robert (OECD Economics Department Working Papers, 1991)
A recent study by David Aschauer suggested a novel explanation for the slowdown of private-sector total factor productivity (TFP) in the United States in the early 1970s. He argues that it is due to the roughly contemporaneous slowdown in the rate of investment in public-sector infrastructure. Using data for eleven OECD countries, this note provides only mixed support for Aschauer's hypothesis. With series starting in the 1960s for most countries, regression analysis found a significant effect of infrastructure on TFP in about half the countries. A longer-term perspective was also examined for the United States. On the basis of data going back to the end of the 19th century, it appears that there was no relationship between infrastructure and TFP until after World War II ...